Combating maritime transnational crime: an Australian perspective. Issue 1 (2nd January 2016) - Noonan, Mike; Williams, Elizabeth
ABSTRACT: Criminals flourish at sea, provided it remains an isolated environment in which they can hide. The longer they remain hidden, the more confident they become and the more robust their illegal operations. As all governments in these economic times attempt to make the most out of the least, the most effective mechanisms for the region to be able to interdict crimes at sea, is to share information, and most importantly, ensure that we are working on the same solution to what is a shared problem. Australia's experience in three areas, illegal, unreported and unregulated fishing, assisted illegal migration and maritime counter terrorism, provides examples of why information sharing and a cooperative stance is so important for nations of the Indian Ocean region.